Blooming vegetable industry in India - Naik, Prakash S; Swami, Vanithha; Koley, Tamnay (Indian Horticulture, 2019)
Vegetables are an important component of agriculture and human diet. Improving infrastructural facilities and having critical policy changes have become important to attract investments to this sector. Vegetable industry has huge potential to create direct and indirect employment opportunities and foreign exchange. Creating awareness among farmers regarding quality production of vegetables and encouraging peri-urban farming, kitchen gardening, organic farming, contract farming, off-season and protected cultivation and precision farming in vegetables have become necessary. Publicprivate partnership, farmers’ cooperatives, small-scale agri-business enterprises for processing of vegetables should be encouraged.